Relational Capability and Commitment of Extractive Industry Corporate Social Responsibility (CSR) Programs: A Case Study on A Geothermal Company in Sukabumi Regency, West Java - Kautsar, Fiel (UI Scholars Hub, 2018)
Corporate Social Responsibility (CSR) programs in extractive industries in Indonesia, which grew rapidly in the post-New Order era, can be seen as a means to develop local communities. However, such programs tend to be unilateral (one-sided), and leading to problems, because they often do not represent the expectations and needs of local communities. Previous studies about unilateral CSR in extractive industries categorized the programs into two types according to their substances: CSR as charity and CSR as mandatory. This article rejects both categories, as they do not optimally develop the local community. This article argues that the justice in CSR programs in extractive industries, as a means to develop local communities, can be achieved through relational capability and commitment. This article is written based on a the qualitative approach and conducts a case study on the CSR program of a geothermal company in Sukabumi Regency, West Java, Indonesia